تحسين أداء خوارزمية توفير الطّاقة الديناميكية في الهواتفِ الذّكية (Latakia University Journal -Engineering Sciences Series, 2018)
تُعتبر خوارزميات توفير الطّاقة المُستهلكة من قبل تقنية Wi-Fi (الستاتيكية والديناميكية) مُساهم قوي في تحسينِ زمنِ تفريغِ بطاريةِ الهواتفِ الذّكية، إلاّ أنَّ أحدَ أهمِ العوامل التّي قد تُؤثّر على أدائِها، هو زيادة عدد الهواتف الذّكية المُتنافِسة على النفاذِ إلى الوسطِ اللاسلكي. اقترحَ هذا البحث تحسيناً للخوارزميةِ الديناميكية، بحيث تمَّ استغلال معيار خاص بالشبكة اللاسلكية (قوة الإشارة المُستقبلة)، لإنقاصِ مُستوى الازدحامِ الشبكي، وهذا ما يترك أثراً إيجابياً على كل من الطّاقة المُستهلكة، ومعاييرِ جودةِ الخدمة المطلوبة للتطبيقاتِ الشبكية.تمَّ التحقّق من الخوارزميةِ المُقترحة (RS-DPSM)، عن طريقِ مقارنةِ أدائِها معَ أداءِ خوارزمياتِ توفيرِ الطّاقة القياسية، وذلكَ باستخدامِ المُحاكي NS-2، وقد أظهرت النتائج تفوّقاً ملحوظاً للخوارزميةِ المُقترحة في أغلبِ السيناريوهات.Power Saving algorithms consumed by Wi-Fi technology (static and dynamic) are considered an essential contributor in improving the battery discharge time in smart phones, Meanwhile, one of most major factors which may affect their performance is that many more numbers of smart phones competing to access into the wireless medium. This research has suggested an improvement for the dynamic algorithm, where one special metric for wireless network is going to be used (the received signal strength), in order to decrease the network congestion, and this results in positive effects on both of consumed power and quality of service metrics required for network applications. Then verifying of the proposed algorithm (RS-DPSM), by comparing its performance with the performance of standard power saving algorithms, through using the simulator NS-2.The results showed a marked superiority of the proposed algorithm in most scenarios.